Strengthening stroke prevention and awareness in the Philippines: a conceptual framework - Sese, Lance Vincent C.; Guillermo, Ma. Celina L. (Frontiers in Neurology, 2023)
Stroke is a leading cause of mortality and disability worldwide, with low and middle-income countries bearing the greatest burden. This article focuses on stroke prevention and awareness in the Philippines, a country grappling with high stroke incidence and limited healthcare resources.The two-pronged approach presented by the authors aims to address the challenges of stroke care by combining community-based prevention and targeted public awareness campaigns. The communitybased stroke prevention component involves personalized risk factor assessments and tailored interventions conducted at local health centers. By identifying modifiable risk factors such as hypertension, diabetes, smoking, and elevated cholesterol levels, healthcare professionals can provide targeted education and interventions to individuals at risk. Additionally, the decentralized targeted stroke awareness campaigns emphasize public education through culturally adapted materials, engagement with local stakeholders, and media campaigns. These initiatives seek to increase awareness of stroke symptoms and prompt presentation in medical facilities.By implementing this comprehensive approach, we aim to mitigate the burden of stroke in the Philippines, improve stroke outcomes, and raise public awareness about stroke recognition and prevention.